آیاتِ متعارضہ (بظاہر)کے تناظر میں تفسیر معارف القرآن اور تفسیر ضیاء القرآن کاتقابلی جائزہ: A Comparative Analysis of Tafsīr Mʻārif Ul-Qur’ān & Tafsīr Zia ul-Qur’ān in the Context of (Apparent) Conflicting Verses - Sajjad, Muhammad; Haider, Dr. Ghulam (Al-Amīr Research Journal for Islamic Studies, 2024)
Islam is a complete code of life.This is a reality that the last revealed book Holy Quran is a permanent source of guidance for humanity till the day of judgement. Sometimes it seems as if there are some contradictory verses but the reality is that there is no contradiction in the verses of the last book.The paper will remove this misunderstanding from the minds of people.The exegises of two prominent theologians of sub-continent are taken into consideration.Both the scholars make it clear with arguments that Holy Quran is free from all types of contradiction.Descriptive and analytical research methodology is adopted in the article.Brief introduction of both Mufassireen and their tafaseer is given.Eight apparent contradictions are selected and analyzed.Mufti Muhammad Shaf ‘i and Peer Muhammad Karam Shah pondered over the last book with the help of narrations of Holy Prophet(SAWS).Moreover both were equipped with the knowledge of Fiqh.That is why they solved the problems of understanding the verses amicably. Keywords: Contradictory verses, Apparent contradiction, Revelation, Exegises.